Effect of solution molarity on microstructural and optical properties of CdCr2S4 thin films - BOYRAZ, CİHAT (ELSEVIER SCI LTD, 2015)
Transparent conducting cadmium chromium sulfide [CdCr2S4, (CCS)] thin films with various precursor molarities were deposited onto Si (100) substrates by simple chemical bath deposition (CBD) process. X-ray diffraction (XRD), scanning electron microscope (SEM), energy dispersive X-ray analysis (EDX), atomic force microscope (AFM), and optical absorption techniques were used to characterize the coated CCS thin films. The XRD exhibits a reasonably crystalline cubic structure that defines the thin film patterns. The molar effect on film quality has also been investigated. The correlation between the molar effect, structural and optical properties reveals that the band gap energy of the thin films is influenced by the size of the crystallites composing the thin films. The roughness of CCS thin films and the roughness-precursor molarity dependence have been established by AFM measurements. Increasing grain size of CCS thin films leads to a shift in the band gap energy from 2.65 to 2.47 eV. The quantum confinement effect should be the reason for possible band gap energy shifts. (c) 2015 Elsevier Ltd. All rights reserved.
Keywords: CdCr2S4 thin films; Microstructure; Band gap energy shifts; COLOSSAL MAGNETORESISTANCE; DEPOSITION